Development of an Entrepreneurship-Based Science Module to Improve Creative Thinking Skills of Junior High School Students - Isnamaini Isnamaini; Irwandi Irwandi; Nopriyeni Nopriyeni (International Forum of Researchers and Lecturers, 2025)
This study aims to develop an entrepreneurship-based science module to enhance the creative thinking skills of students at SMPN 7 Seluma. The development model employed in this study was the ADDIE model. The research subjects were ninth-grade students of SMPN 7 Seluma, with samples consisting of students from classes IX C, IX D, and IX E. The research instruments included expert validation sheets, questionnaires, and pretest and posttest questions. The validation results from experts indicated that the developed entrepreneurship-based science module was valid. In the first trial phase, the module obtained a score of 95%, categorized as very practical. In the second trial phase, the module achieved a score of 96%, also categorized as very practical. The N-gain value of 0.779 in Trial I indicated a high level of improvement in students’ creative thinking skills, while the N-gain value of 0.797 in Trial II also showed a high level of improvement. Therefore, the developed entrepreneurship-based science module is proven to be valid, practical, and effective in enhancing students’ creative thinking skills and can be easily implemented in science learning